Collective existential threat mediates White population decline's effect on defensive reactions. (April 2020) - Bai, Hui; Federico, Christopher M.
We present evidence from two studies probing into whether perceived numerical decline in the White population translate into collective existential threat to Whites, leading in turn to defensive reactions. In Study 1, we used correlational data to show whether collective existential threat mediates the relationship between perceptions of White population decline and defensive political reactions (i.e., racial biases and conservatism) among Whites. In Study 2, we replicate the results of Study 1 experimentally manipulating perceptions of White population decline and growth. Our results suggest that Whites' perceptions of the ingroup's numerical decline have a unique effect on their racial and political attitudes via heightened feelings of collective existential threat.